Frequency of retinal re-detachment after silicone oil removal through posterior capsulotomy combined with phacoemulsification (Journal of Fatima Jinnah Medical University, 2019)
Background: Various techniques are used for the removal of silicone oil from eyes including 2 pars plana ports, 3 pars plana ports technique or through pupil combined with cataract surgery performing posterior capsulotomy which is a relatively newer technique. Retinal redetachment is the most common complication occurring after removal of silicone oil. Purpose of the study was to determine the frequency of retinal redetachment after silicone oil removal through posterior capsulotomy combined with phacoemulsification after rhegmatogenous retinal detachment surgery.Patients and methods: This descriptive study was conducted in Ophthalmology Department Lahore General Hospital, Lahore from February 2017 to February 2018. Total 81 patients having silicone oil with cataract were included. After performing phacoemulsification and cortical aspiration, posterior capsulotomy was made and silicone oil was aspirated followed by a posterior chamber foldable intraocular lens implantation. The outcome was recorded by examining the patients through slit lamp biomicroscope using 90D lens on outdoor basis up to 2 months after removal of silicone oil.Results: Mean age was 38.6 ± 12.5 years. Out of 81 patients, 58 (71.6%) were males and 23 (28.4%) were females with male to female ratio 2.5:1. Frequency of retinal redetachment after silicone oil removal through posterior capsulotomy combined with phacoemulsification was found to be 18.5%.Conclusion: Silicone oil removal through posterior capsulotomy combined with phacoemulsification is a safe and effective technique with no risk of pars plana port break formation and can be performed under local anesthesia in patients having cataract after vitrectomy.
Keywords: Rhegmatogenous retinal detachment; Silicone oil removal,; Phacoemulsification.